Assessing the underreporting of arboviral cases within the Colombian national surveillance program (2019)
Introduction: Chikungunya, dengue, and Zika are three different arboviruses primarily transmitted to humans by Aedes mosquitoes. Historically,Colombiaisoneofthecountriesmostaffectedbychikungunya, dengue, and Zika, with the Aedes mosquito being widely distributed throughout the country at elevations below 2,000 meters, and it is the eighth most highly endemic country in world for dengue. Despite the mandatory reporting of chikungunya, dengue, and Zika, there is signiﬁcant underreporting which has been found for different parts of Colombia and a better understanding of the limitations of that surveillance data in Colombia is crucial to inform its improvement and utility. Aim:Toexamine(scope,natureanddegreeof)underreportingofchikungunya,dengue,andZikacasedatainthenationalsurveillancesystemof Cali,Colombiafrom2014-2017. Methods:Weassessedtheunderreportingofthenationaldiseasesurveillance program, SIVIGILA, in detecting conﬁrmed chikungunya, dengue, and Zika cases through the capture-recapture method, which evaluates the degree of overlap among registries of cases from existing data sources. We evaluate complete captures (e.g., same diagnosis, same information), incomplete captures (e.g., different but relevant diagnosis),inaccurate(e.g.,completemismatchindiagnosis),andnon-existent captures (e.g., does not appear) relative to the SIVIGILA system. We ﬁt multilevel Poisson regression with random effects to determine the predictors of the case being captured within SIVIGILA, using individual (e.g., sex, age, type of diagnostic test) and institutional-level (e.g., public institution,city). Results: In Cali, between 2014-2017 there were 75,963 arboviruses (dengue=54,098; chikungunya=4,423; zika=17,442) reported in Cali, Colombia. Preliminary results showed that 10.6% of vector borne clinically/lab conﬁrmed diseases in private/contributory health care and 8.5%ofthosereportedinthepublic/subsidizedinstitutionswerereported intothesurveillancesystem. Conclusion: Our preliminary analysis has estimated that the underreporting on arboviruses is above than expected and our next step is to identify patient-level and facility-level determinants of underreporting. Identifying the limitations of the surveillance data is crucial for informed sensitivity analyses for disease burden estimates and also in identifying the determinants of poor reporting, which could then be incorporated into further analysis. The complete analysis will provide extremely relevant information to the National Institute of Health to improve the reporting and coverage of the national surveillance program.